Research on potential biomarkers of prostate cancer in Latin America and the Caribbean: a scoping review - Prada, Nicolas J; Mendivelso-González, Daniel; Yepes, Sabrina; Corredor, Carolay; Parra-Medina, Rafael; Varela, Rodolfo; Serrano, Martha Lucía (Frontiers in Oncology, 2026)
BackgroundLatin America and the Caribbean (LAC) have higher prostate cancer (PCa) mortality rates than other regions, possibly due to disparities in detection and treatment, as well as differences in tumor biology and behavior. This scoping review aimed to identify studies conducted in LAC that evaluated potential biomarkers associated with PCa.MethodsA search was conducted in PubMed, Scopus, Embase, LILACS, and Web of Science, including original studies conducted in LAC that evaluated the presence of potential biomarkers in relation to PCa. Due to the heterogeneity of the studies, a descriptive analysis of the data was performed.ResultsA total of 138 articles were included, evaluating 342 potential biomarkers across 17 countries/territories of LAC. Articles were classified into one or more of the following categories of potential biomarkers: risk of developing PCa (n=74), screening, early detection, and diagnosis (n=13), prognosis (n=48), treatment (n=10) and others (n=12). The countries with the most publications were Brazil, Mexico, and Chile.ConclusionMost studies analyzed the relationship between various potential biomarkers and the risk of developing PCa as well as its prognosis. The majority of studies came from continental countries with lower percentages of African ancestry and lower PCa mortality rates, highlighting the need to strengthen research in LAC while improving access to healthcare. Systematic review registration: